2006
DOI: 10.1152/ajpheart.00155.2006
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cell transplantation: preventing apoptosis increases cell survival and ventricular function

Abstract: Cell transplantation prevents cardiac dysfunction after myocardial infarction. However, because most implanted cells are lost to ischemia and apoptosis, the benefits of cell transplantation on heart function could be improved by increasing cell survival. To examine this possibility, male Lewis rat aortic smooth muscle cells (SMCs; 4 ϫ 10 6 ) were pretreated with antiapoptotic Bcl-2 gene transfection or heat shock and then implanted into the infarcted myocardium of anesthetized, syngenic female rats (n ϭ 23 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…ASC sheets also improved systolic and diastolic functions of the MI hearts without their differentiation to cardiac myocytes. These results indicated that paracrine effects, especially, these of VEGF secreted from ASC sheets could be responsible for improvement of the cardiac contraction, since VEGF-dependent angiogenesis has been reported to contribute to cardiac contractile reserve after MI (13). Unfortunately, ASC as well as myoblast cell sheets failed to restore cardiac contractile responses to β-adrenergic stimulation.…”
Section: Measurement Of Cardiac Function In Isolated Perfused Heartsmentioning
confidence: 96%
See 1 more Smart Citation
“…ASC sheets also improved systolic and diastolic functions of the MI hearts without their differentiation to cardiac myocytes. These results indicated that paracrine effects, especially, these of VEGF secreted from ASC sheets could be responsible for improvement of the cardiac contraction, since VEGF-dependent angiogenesis has been reported to contribute to cardiac contractile reserve after MI (13). Unfortunately, ASC as well as myoblast cell sheets failed to restore cardiac contractile responses to β-adrenergic stimulation.…”
Section: Measurement Of Cardiac Function In Isolated Perfused Heartsmentioning
confidence: 96%
“…Each data of three groups were obtained from 6 independent experiments. cell survival and ventricular function (13), ASC sheets were expected to have a higher tolerance for ischemia and hypoxia than myoblast cell sheets, when they were transplanted into MI hearts. However, in in vivo study, there were not any significant differences in restoration of cardiac function and cardiac remodeling between ASC and myoblast cell sheets, suggesting that secretion of higher concentration of angiogenic factors from ASC sheets might not overcome the benefit of myoblast cell sheets (20).…”
Section: Measurement Of Cardiac Function In Isolated Perfused Heartsmentioning
confidence: 99%
“…In addition, the survival rate of transplanted human mesenchymal stem cells in a mouse heart reaches <0.5% at 4 days after transplantation [165]. These discouraging results were also reported using different cell types, such as skeletal myoblasts, smooth muscle cells and unfractionated bone marrow cells, which can survive only few days after transplantation [166][167][168]. In vivo, bone marrow-derived circulating mesenchymal stem cells are able to repopulate damaged tissues, leading to reconstruction of their function, due to the secretion of soluble factors exerting proliferative and anti-apoptotic actions [169].…”
Section: Cell-based Therapies and Anoikismentioning
confidence: 98%
“…Bcl-2 inhibits cell death by blocking cytochrome C release from the mitochondria [67], that otherwise leads to caspase activation and cell death. Bcl-2 is up-regulated in surviving ventricular myocytes in the context of MI [68], and transgenic over-expression of Bcl-2 in the engrafted cells limits myocardial infarct size after ischemia/reperfusion [69]. Li and colleagues have demonstrated the pro-survival effects of transduced Bcl-2 in two cell types: smooth muscle cells [69] and mesenchymal stem cells [70].…”
Section: Strategies To Increase Cell Survivalmentioning
confidence: 99%
“…Bcl-2 is up-regulated in surviving ventricular myocytes in the context of MI [68], and transgenic over-expression of Bcl-2 in the engrafted cells limits myocardial infarct size after ischemia/reperfusion [69]. Li and colleagues have demonstrated the pro-survival effects of transduced Bcl-2 in two cell types: smooth muscle cells [69] and mesenchymal stem cells [70]. In each case, engraftment was improved as measured by cell graft size and ventricular function.…”
Section: Strategies To Increase Cell Survivalmentioning
confidence: 99%